PERAN PEMERINTAH DAN ORGANISASI PROFESI YANG IDEAL DALAM SEKTOR KESEHATAN BERDASARKAN RUU OMNIBUSLAW - Riskha Dora Candra Dewi (EDUPEDIA Publisher, 2023)
Objective: This research aims to examine the ideal role of government and professional organizations in the health sector based on the Omnibus Law. Methods: This research uses normative legal research methods that combine analytical, conceptual and legal perspectives. Results: The study findings show that the Health Omnibus Law is also considered a national legal plan to improve the health of the Indonesian people, primarily through foreign trade in the field of health services. Therefore, updating and harmonizing national laws and regulations is very important while still adhering to the values of Pancasila. Conclusion: The government is primarily responsible for planning, organizing, and managing health programs that are equitable and affordable for everyone. It is hoped that the Omnibus Law on Health will fulfill people's expectations of getting good health services while still fulfilling the government's obligations towards the health of Indonesian citizens. Unifying and updating national legal regulations is the key to improving public health while still paying attention to the values of Pancasila so that public health can be improved fairly and safely in accordance with the law.